Populist Understandings of the Law: A Conservative Backlash? - Blokker, Paul (PARTECIPAZIONE E CONFLITTO, 2020)
The main argument is that the contemporary manifestations of right-wing populism in Europe ought to be understood, at least in part, as reactions to a distinctive form of postwar European society, which I will call here embedded constitutional democracy. The argument is that the populist reaction to embedded constitutional democracy generally takes a conservative form. This conservatism is expressed in rather different ways (ranging from ethnoreligious views to 'illiberal liberal' ones), but at the same time populism displays a shared core of criticisms on liberalism, and in particular regarding the internationalized or global version of liberalism. In the article, I will start with a brief analysis of the emergence of postwar society in the form of embedded constitutional democracy, used as a backcloth for the subsequent discussion of critical views of liberal understandings of the law in conservative populist thinking. I will, then, focus on populists' critical views of liberalism and 'globalism', analyzed in the form of contemporary articulations of (conservative) populism in both East-Central Europe (Hungary and Poland), and Western Europe (France, Italy, the Netherlands). In order to identify ideological affinities and critical positions, I discuss four themes: abstractness and inauthenticity, identity threat, domination, and legal fundamentalism.